Epidemiology of Lyme Disease Diagnoses among Older Adults, United States, 2016–2019 - Amy M. Schwartz; Christina A. Nelson; Alison F. Hinckley (Emerging Infectious Diseases, 2024)
We used Medicare data to identify >88,000 adults >65 years of age diagnosed and treated for Lyme disease during 2016–2019 in the United States. Most diagnoses occurred among residents of high-incidence states, in summer, and among men. Incidence of diagnoses was substantially higher than that reported through public health surveillance.